2020
DOI: 10.1101/2020.03.30.016451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipid Droplets in Brown Adipose Tissue Are Dispensable for Cold-Induced Thermogenesis

Abstract: Brown adipocytes store metabolic energy as triglycerides (TG) in multilocular lipid droplets (LDs). Fatty acids released from brown adipocyte LDs by lipolysis are thought to activate and fuel UCP1-mediated thermogenesis. Here we test this hypothesis by preventing fatty acid storage in murine brown adipocytes through brown adipose tissue (BAT)-specific deletions of the TG synthesis enzymes, DGAT1 and DGAT2 (BA-DGAT KO). Despite the absence of LDs, BA-DGAT KO mice had functional BAT and maintained euthermia duri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…Furthermore, a null mutation in ADRB3 in mice largely impairs the stimulated lipolytic activity of BAT (Preitner et al, 1998). These data and other reports demonstrate that, although BAT can perform lipolysis, it is not necessary for responding to IF or cold exposure, where knockout of key lipolysis or lipogenesis did not inhibit BAT thermogenesis (Chitraju et al, 2020;Shin et al, 2017). In these situations, BAT relies more on free fatty acids and glucose from WAT.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, a null mutation in ADRB3 in mice largely impairs the stimulated lipolytic activity of BAT (Preitner et al, 1998). These data and other reports demonstrate that, although BAT can perform lipolysis, it is not necessary for responding to IF or cold exposure, where knockout of key lipolysis or lipogenesis did not inhibit BAT thermogenesis (Chitraju et al, 2020;Shin et al, 2017). In these situations, BAT relies more on free fatty acids and glucose from WAT.…”
Section: Discussionsupporting
confidence: 66%
“…Recent studies have challenged the popular idea that lipolysis and lipid droplets in brown adipocytes are required for BAT thermogenesis. There is increasing evidence that WAT lipolysis is required to fuel non-shivering thermogenesis during fasting conditions (Schreiber et al, 2017;Shin et al, 2017;Chitraju et al, 2020). Consistent with this notion, our data indicate that liver AKT-FOXO1 signaling is required for proper catecholamine-induced lipolysis and defense of body temperature during an acute cold challenge.…”
Section: Discussionsupporting
confidence: 86%
“…The presence of smaller lipid droplets in the BAT from mice lacking HuR is interesting and suggestive of a possible fuel shortage mechanism in BAT from Adipo-HuR −/mice. However, it has been shown that lipolysis of lipid droplets within BAT is not required for thermogenesis [34] and, more recently, that lipid droplets within BAT are entirely dispensable for cold-induced thermogenesis [35].…”
Section: Discussionmentioning
confidence: 99%